2017
DOI: 10.11604/pamj.2017.28.314.10203
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: descriptive profile of 80 women attending breast cancer care in the Department of General and Digestive Surgery of CHU-YO

Abstract: IntroductionBreast cancer is a common cause of death among women in Burkina Faso. The aim of this study was to determine a descriptive profile of 80 women and establish a description of risk factors associated with breast cancer in these women.MethodsThis cross-sectional study recruited women with breast cancer in Ouagadougou. Teaching Hospital Yalgado Ouedraogo in Burkina Faso from January 2015 to February 2016. We have collected data on socio-demographic characteristics, reproductive status, clinical informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
(11 reference statements)
2
9
2
1
Order By: Relevance
“…Several well-known risk factors for breast cancer development are family history of breast cancer, advanced age, early puberty, late menopause, nulliparity, obesity and hereditary transmission of certain predisposition genes, including the BRCA1 and BRCA2 genes (involved in 5-10% of breast cancer cases) and the CHEK2, TP53, ATM and PTEN genes [1,3,4]. In Burkina Faso, previous studies have described the distribution of breast cancer risk factors in a population [5] and shown that multiparity is associated with a decreased risk of breast cancer [6]. Genetic analyses targeting relevant exons in BRCA1 genes have also been performed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several well-known risk factors for breast cancer development are family history of breast cancer, advanced age, early puberty, late menopause, nulliparity, obesity and hereditary transmission of certain predisposition genes, including the BRCA1 and BRCA2 genes (involved in 5-10% of breast cancer cases) and the CHEK2, TP53, ATM and PTEN genes [1,3,4]. In Burkina Faso, previous studies have described the distribution of breast cancer risk factors in a population [5] and shown that multiparity is associated with a decreased risk of breast cancer [6]. Genetic analyses targeting relevant exons in BRCA1 genes have also been performed [7].…”
Section: Introductionmentioning
confidence: 99%
“…The education for self-examination and awareness of the population would allow earlier diagnosis. Lastly, breast cancer was diagnosed at late presentation (stage II, III and IV) constituted 93.75 % of cases [40]. In Burkina Faso, patients often resort to traditional medicine or other treatments before coming to a consultation.…”
Section: Burkina Fasomentioning
confidence: 99%
“…In Burkina Faso (one of the west African countries) breast cancer is being responsible for 17.7% of women's deaths [7]. A recent study provide preliminary information about breast cancer risk decreasing with multiparity among women in Burkina Faso [8,9]. Genetic and non-genetic factors are involved in the etiology of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The available information about breast cancer in Burkina Faso, regarding the histo-pathological characteristics of tumors and parity risk factors, is limited [8,9], with few specific records about genetic features [8,9,21].…”
Section: Introductionmentioning
confidence: 99%